Negative electrode slurry, negative electrode pole piece and lithium ion battery thereof

By using the three-dimensional network structure formed by furyl hollow polyamide fibers in the negative electrode material of lithium batteries, the problem of volume expansion and contraction of silicon-based materials during charging and discharging is solved, and the circulation performance and Coulomb efficiency of lithium batteries are significantly improved.

CN119725509APending Publication Date: 2025-03-28ANHUI LIKE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411822261.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The silicon-based negative electrode material will undergo severe volume expansion and contraction during the charging and discharging of lithium batteries, resulting in a decrease in battery circulation performance and Coulomb efficiency.

Method used

A negative electrode slurry is used, which includes 85 to 95 parts by mass of silicon-based negative electrode active material, 10 to 25 parts by mass of furyl hollow polyamide fiber, 2 to 5 parts by mass of binder, 0.5 to 2 parts by mass of conductive agent, and 3 to 6 parts by mass of first solvent. Furanyl hollow polyamide fibers are prepared by electrospinning technology to form a hollow structure, increase the surface area, form a three-dimensional network structure combined with silicon-based materials, and alleviate physical stress during charging and discharging.

Benefits of technology

By improving the surface area and stability of the silicon-based negative electrode material, reducing the volume expansion effect, improving the conductivity of the negative electrode sheet, and significantly improving the circulation performance and Coulomb efficiency of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725509A_ABST
    Figure CN119725509A_ABST
Patent Text Reader

Abstract

The invention discloses negative electrode slurry, a negative electrode pole piece and a lithium ion battery thereof. The negative electrode slurry comprises the following components in parts by mass: 85-95 parts of a negative electrode active material, 10-25 parts of furyl hollow polyamide fiber, 2-5 parts of a binder, 0.5-2 parts of a conductive agent and 3-6 parts of a solvent. The negative electrode slurry comprises a silicon-based negative electrode active material, furyl hollow polyamide fibers, a binder, a conductive agent and a solvent, and furyl hollow polyamide contains amide groups and can form a three-dimensional network structure with a silicon-based material, so that the silicon-based negative electrode active material has high specific area and higher stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to negative electrode slurry, negative electrode plates and lithium ion batteries thereof. Background Art

[0002] Since the successful commercialization of lithium cobalt oxide batteries by Sony Corporation of Japan in the 1990s, lithium-ion batteries have continued to develop over the past 30 years and are widely used in new energy vehicles, smart phones, energy storage power stations and other fields, providing many conveniences for people's lives. Lithium-ion batteries are generally composed of a positive electrode, a negative electrode, a separator and an electrolyte.

[0003] In the battery structure, the positive and negative electrode materials have the greatest impact on the battery capacity. Among them, graphite is currently the most widely used negative electrode material in commercial use, but its specific capacity is limited and it is difficult to meet people's requirements for the energy density of lithium batteries. In comparison, silicon-based negative electrode materials have higher specific capacity and broad prospects, and are considered to be the most likely negative electrode materials to replace graphite. However, silicon-based materials will experience severe volume expansion and contraction during the battery charging and discharging process, which seriously restricts the battery's cycle performance. In order to solve this technical problem of silicon-based materials, carbon layers are usually used to coat silicon-based materials to reduce the volume effect of silicon, but the mitigation effect is poor. At the same time, in the process of using carbon layers for coating, high-temperature procedures such as calcination are required. The high-temperature process will reduce the performance of the material. In addition, the carbonized carbon source cannot be evenly coated on the silicon-based material. Direct application to the battery will reduce the battery's cycle performance and coulombic efficiency. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a negative electrode slurry, a negative electrode sheet and a lithium ion battery thereof, wherein the negative electrode slurry can reduce the volume expansion effect of the negative electrode material, improve the conductivity of the negative electrode sheet, and thus improve the cycle performance and coulomb efficiency of the battery.

[0005] In one aspect of the present invention, the present invention provides a negative electrode slurry, the negative electrode slurry comprising:

[0006] 85-95 parts by mass of silicon-based negative electrode active material, 10-25 parts by mass of furan-based hollow polyamide fiber, 2-5 parts by mass of binder, 0.5-2 parts by mass of conductive agent and 3-6 parts by mass of first solvent.

[0007] The negative electrode slurry includes silicon-based negative electrode active materials, furan-based hollow polyamide fibers, binders, conductive agents and solvents. The furan-based hollow polyamide contains amide groups, which can form a three-dimensional network structure with the silicon-based materials, so that the silicon-based negative electrode active materials have a high specific area and are more stable.

[0008] In some embodiments of the present invention, the preparation method of the furan-based hollow polyamide fiber includes: (1) diluting the furan-based polyamide solution to obtain a cortex solution with a mass fraction of 5 to 15 wt%; (2) dissolving octadecane in alcohol to obtain a core solution with a mass fraction of 5 to 20 wt%; (3) injecting the cortex solution and the core solution into a syringe respectively, and then connecting the outer needle and the inner needle of the coaxial needle respectively, spinning on an electrospinning machine, and then drying, and then removing octadecane to obtain furan-based hollow polyamide fiber.

[0009] The furan-based hollow polyamide fiber prepared by this method has a hollow structure and a large surface area, which provides more free space for the silicon-based negative electrode material, relieves the physical stress generated during the charging and discharging process, increases the contact area with the electrolyte, and improves the wettability to the electrolyte, thereby improving the cycle performance and coulombic efficiency of the lithium battery.

[0010] In addition, the negative electrode slurry of the present invention may also have the following additional technical features:

[0011] In some embodiments of the present invention, in step (1), the method for preparing the furan-based polyamide solution comprises: mixing a dibasic acid containing a furan ring structure or an acyl chloride containing a furan ring structure, a diamine containing a benzene ring structure and a second solvent under an inert atmosphere, and obtaining a furan-based polyamide solution after polymerization.

[0012] In some embodiments of the present invention, the molar ratio of the dibasic acid containing a furan ring structure or the acyl chloride containing a furan ring structure to the diamine containing a benzene ring structure is (1-1.2):1.

[0013] In some embodiments of the present invention, the mass ratio of the diamine containing a benzene ring structure to the second solvent is 1:(4-10).

[0014] In some embodiments of the present invention, the mass ratio of the octadecane to the alcohol is (5-20):100.

[0015] In some embodiments of the present invention, the dibasic acid containing a furan ring structure is one or both of 2,5-furandicarboxylic acid and 3,4-furandicarboxylic acid, and the acyl chloride containing a furan ring structure is furandicarboxylic acid chloride.

[0016] In some embodiments of the present invention, the diamine containing a benzene ring structure is one or more of p-phenylenediamine, m-phenylenediamine, 2,5-diaminobenzenesulfonic acid and 4,4-diaminodiphenyl ether.

[0017] In some embodiments of the present invention, in step (3), spinning is performed on an electrospinning machine at 15 to 20 kV, with a spinning distance of 12 to 15 cm, a spinning temperature of 30 to 60° C., a relative humidity of 40 to 50%, and a spinning time of 4 to 10 h.

[0018] In some embodiments of the present invention, the feeding rate of the skin layer solution is 0.4-3 mL / h, and the feeding rate of the core layer solution is 0.08-0.3 mL / h.

[0019] In some embodiments of the present invention, the binder is one or more of styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone and polytetrafluoroethylene.

[0020] In some embodiments of the present invention, the conductive agent is one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.

[0021] In some embodiments of the present invention, the first solvent and the second solvent independently include one or more of water, N-methylpyrrolidone, dimethylformamide, diethylformamide, dimethyl sulfoxide and 1,5-dimethyl-2-pyrrolidone.

[0022] In the second aspect of the present invention, the present invention provides a negative electrode plate, the negative electrode plate comprising: a negative electrode current collector; a coating, the coating is provided on the negative electrode current collector, and the coating is formed by coating the above-mentioned negative electrode slurry on the negative electrode current collector. The conductivity of the negative electrode plate obtained thereby is improved, the coating is compact, and the expansion is reduced.

[0023] In a third aspect of the present invention, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the above-mentioned negative electrode sheet, and the cycle performance and coulombic efficiency of the lithium-ion battery obtained thereby are improved.

[0024] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0026] Figure 1 This is a SEM image of the furan-based hollow polyamide fiber prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0028] Example 1

[0029] 1. Preparation of furan-based polyamide solution: Under a nitrogen atmosphere, 2,5-furandicarboxylic acid and p-phenylenediamine were dissolved in N-methylpyrrolidone at a molar ratio of 1.1:1 and reacted for 4 hours. The mass ratio of p-phenylenediamine to N-methylpyrrolidone was 1:4 to obtain a furan-based polyamide solution.

[0030] 2. Preparation of furan-based hollow polyamide fibers:

[0031] (1) diluting the prepared furan-based polyamide solution to obtain a cortex solution with a mass fraction of 6 wt %;

[0032] (2) dissolving octadecane in ethanol to obtain a core layer solution with a mass fraction of 5 wt %;

[0033] (3) The skin solution and the core solution were injected into 10 mL syringes respectively, with the skin solution feeding rate of 0.5 mL / h and the core solution feeding rate of 0.1 mL / h. Then, the outer needle with an inner diameter of 1.01 mm and an outer diameter of 1.49 mm and the inner needle with an inner diameter of 0.41 mm and an outer diameter of 0.72 mm were connected to the coaxial needle respectively, and spinning was performed on an electrospinning machine. The spinning parameters were as follows: the ambient temperature was controlled at 50°C, the relative humidity was 45%, the spinning was performed at 15 kV, the spinning distance was 12 cm, and the spinning time was 4 h. Then, the spinning was dried for 24 h to remove the residual solvent, and then the octadecane was removed to obtain hollow furan-based polyamide nanofibers. The SEM image of the obtained hollow fiber is shown in FIG. Figure 1 .

[0034] 3. Prepare negative electrode slurry: 86 parts by mass of silicon particles, 12 parts by mass of the prepared furan-based hollow polyamide fiber, 2 parts by mass of polytetrafluoroethylene, 0.6 parts by mass of conductive graphite and 3 parts by mass of N-methylpyrrolidone are mixed and stirred evenly to obtain negative electrode slurry.

[0035] 4. Prepare the negative electrode sheet: evenly coat the negative electrode slurry on both sides of the copper foil and dry it to obtain the negative electrode sheet.

[0036] 5. Prepare lithium battery: Pair the above negative electrode sheet with the lithium sheet to prepare a button battery.

[0037] Example 2

[0038] 1. Preparation of furan-based polyamide solution: Replace furandicarboxylic acid with furandicarboxylic acid chloride, and the rest of the process is the same as Example 1.

[0039] 2. Preparation of furan-based hollow polyamide fibers: Same as Example 1.

[0040] 3. Prepare negative electrode slurry: replace the negative electrode active material with SiO, replace the binder with styrene-butadiene rubber, replace the conductive agent with carbon nanotubes, and follow the same process as in Example 1 to prepare negative electrode slurry.

[0041] 4. Preparation of negative electrode sheet: same as in Example 1.

[0042] 5. Preparation of lithium battery: same as in Example 1.

[0043] Example 3

[0044] 1. Preparation of furan-based polyamide solution: Same as Example 2.

[0045] 2. Preparation of furan-based hollow polyamide fibers: Same as Example 2.

[0046] 3. Prepare negative electrode slurry: 94 parts by mass of silicon particles, 25 parts by mass of the prepared furan-based hollow polyamide fiber, 5 parts by mass of polytetrafluoroethylene, 1.9 parts by mass of conductive graphite and 6 parts by mass of N-methylpyrrolidone are mixed and stirred evenly to obtain negative electrode slurry.

[0047] 4. Preparation of negative electrode sheet: same as in Example 2.

[0048] 5. Preparation of lithium battery: same as Example 2.

[0049] Example 4

[0050] 1. Preparation of furan-based polyamide solution: Under nitrogen atmosphere, 2,5-furandicarboxylic acid chloride and m-phenylenediamine were dissolved in N,N-dimethylformamide at a molar ratio of 1.1:1 and reacted for 4 hours. The mass ratio of m-phenylenediamine to N,N-dimethylformamide was 1:4 to obtain a furan-based polyamide solution.

[0051] 2. Preparation of furan-based hollow polyamide fibers: Same as Example 1.

[0052] 3. Preparation of negative electrode slurry: same as in Example 1.

[0053] 4. Preparation of negative electrode sheet: same as in Example 1.

[0054] 5. Preparation of lithium battery: same as in Example 1.

[0055] Comparative Example 1

[0056] 1. Preparation of furan-based polyamide solution: Same as Example 1.

[0057] 2. Preparation of furan-based hollow polyamide fibers: Same as Example 1.

[0058] 3. Prepare negative electrode slurry: Replace silicon particles with commonly used graphite, and follow the same process as in Example 1 to prepare negative electrode slurry.

[0059] 4. Preparation of negative electrode sheet: same as in Example 1.

[0060] 5. Preparation of lithium battery: same as in Example 1.

[0061] Comparative Example 2

[0062] 1. Preparation of furan-based polyamide solution: Same as Example 1.

[0063] 2. Prepare negative electrode slurry: replace the furan-based hollow polyamide fiber with a furan-based polyamide solution, and follow the same procedures as in Example 1 to prepare negative electrode slurry.

[0064] 3. Preparation of negative electrode sheet: same as in Example 1.

[0065] 4. Preparation of lithium battery: same as in Example 1.

[0066] Comparative Example 3

[0067] 1. Prepare negative electrode slurry: 86 parts by mass of silicon particles, 2 parts by mass of polytetrafluoroethylene, 0.6 parts by mass of conductive graphite and 3 parts by mass of N-methylpyrrolidone are mixed and stirred evenly to obtain negative electrode slurry.

[0068] 2. Prepare the negative electrode sheet: evenly coat the negative electrode slurry obtained above on both sides of the copper foil, dry it, and obtain the negative electrode sheet.

[0069] 3. Prepare lithium battery: Pair the above negative electrode sheet with the lithium sheet to prepare a button battery.

[0070] The electrochemical performance test of the batteries prepared in Examples 1-4 and Comparative Examples 1-3 was conducted below. The charge and discharge cycle test was conducted at a 1C rate, the voltage setting range was 0-1.5V, the number of cycles was 200, and the rate performance test was conducted at a 2C rate. The batteries after 100 cycles were disassembled, and the expansion rate of the corresponding negative electrode plates was measured. The test results are recorded in Table 1.

[0071] Table 1

[0072]

[0073] As can be seen from Table 1, the negative electrode sheets prepared in Examples 1-4 have high first-cycle coulomb efficiency and stable cyclability, and low expansion rate. In Comparative Example 1, due to the lack of silicon, a three-dimensional network structure cannot be formed, and the performance of the battery is significantly reduced; in Comparative Example 2, the lack of hollow fibers will also reduce the surface area of ​​the entire negative electrode sheet, which is not conducive to alleviating the expansion effect of silicon materials; in Comparative Example 3, there is no three-dimensional network structure and the formation of hollow fibers, and the expansion effect of the negative electrode sheet is significantly increased.

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A negative electrode slurry, characterized in that: include: 85-95 parts by mass of silicon-based negative electrode active material, 10-25 parts by mass of furan-based hollow polyamide fiber, 2-5 parts by mass of binder, 0.5-2 parts by mass of conductive agent and 3-6 parts by mass of first solvent.

2. The negative electrode slurry according to claim 1, characterized in that The preparation method of the furan-based hollow polyamide fiber comprises: (1) diluting the furan-based polyamide solution to obtain a cortex solution having a mass fraction of 5 to 15 wt %; (2) dissolving octadecane in alcohol to obtain a core layer solution with a mass fraction of 5 to 20 wt %; (3) The skin layer solution and the core layer solution are respectively injected into a syringe, and then the outer needle and the inner needle of the coaxial needle are respectively connected, and spinning is performed on an electrospinning machine, followed by drying and removing octadecane to obtain furan-based hollow polyamide fibers.

3. The negative electrode slurry according to claim 2, characterized in that: In step (1), the method for preparing the furan-based polyamide solution comprises: mixing a dibasic acid containing a furan ring structure or an acyl chloride containing a furan ring structure, a diamine containing a benzene ring structure and a second solvent under an inert atmosphere, and obtaining a furan-based polyamide solution after polymerization.

4. The negative electrode slurry according to claim 3, characterized in that: The molar ratio of the furan ring-containing dibasic acid or the furan ring-containing acyl chloride to the diamine containing a benzene ring structure is (1-1.2):1; the mass ratio of the diamine containing a benzene ring structure to the second solvent is 1:(4-10).

5. The negative electrode slurry according to claim 3, characterized in that: The furan ring structure-containing dibasic acid is one or two of 2,5-furandicarboxylic acid and 3,4-furandicarboxylic acid; the furan ring structure-containing acyl chloride is furandicarboxylic acid chloride; and the benzene ring structure-containing diamine is one or more of p-phenylenediamine, m-phenylenediamine, 2,5-diaminobenzenesulfonic acid and 4,4-diaminodiphenyl ether.

6. The negative electrode slurry according to claim 2, characterized in that: In step (3), spinning is performed on an electrospinning machine at 15 to 20 kV, a spinning distance of 12 to 15 cm, a spinning temperature of 30 to 60° C., a relative humidity of 40 to 50%, and a spinning time of 4 to 10 hours.

7. The negative electrode slurry according to claim 2, characterized in that: The feeding rate of the skin layer solution is 0.4-3 mL / h, and the feeding rate of the core layer solution is 0.08-0.3 mL / h.

8. The negative electrode slurry according to claim 3, characterized in that: The silicon-based negative electrode active material is one or more of silicon oxide, silicon particles and silicon-carbon composite materials; The binder is one or more of styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone and polytetrafluoroethylene; The conductive agent is one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene; The first solvent and the second solvent independently include one or more of water, N-methylpyrrolidone, dimethylformamide, diethylformamide, dimethyl sulfoxide and 1,5-dimethyl-2-pyrrolidone.

9. A negative electrode plate, characterized in that: include: Anode current collector; A coating, wherein the coating is disposed on the negative electrode current collector, and the coating is formed by coating the negative electrode slurry according to any one of claims 1 to 8 on the negative electrode current collector.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.